Manajemen Akuntansi Hijau Dalam Efisiensi Biaya Lingkungan Studi Pada Pt. Coca Cola Bottling Indonesia Tanjung Bintang - Bagas, Muhammad Adi; Riani, Novi; Ekawati, Farida (JOURNAL OF INTERDISCIPLINARY SCIENCE AND EDUCATION, 2023)
This study explores the implementation of green accounting at PT. Coca-Cola Bottling Indonesia Tanjung Bintang Suda Lampung, highlighting its role in environmental sustainability and business performance. Green accounting transcends traditional cost accounting by incorporating environmental factors like air and water pollution, waste management, and resource utilization. By evaluating environmental activities and their associated costs, it encourages companies to identify hidden costs, improve efficiency, and ultimately reduce environmental impact. This research analyzes PT. Coca-Cola's green accounting approach through a descriptive qualitative lens, interviewing key personnel and examining relevant documents. The findings reveal that the company utilizes green accounting as a tool for efficient resource allocation and informed decision-making. It provides valuable financial data and performance indicators, enabling managers to identify cost-saving opportunities and enhance environmental responsibility. Furthermore, PT. Coca-Cola effectively communicates its green accounting practices to stakeholders, including regulators, investors, and the local community. This transparency fosters trust and contributes to positive relationships with external parties. Beyond direct cost savings, PT. Coca-Cola recognizes the long-term benefits of environmental protection. Reduced environmental damage enhances brand reputation, attracts responsible investors, and secures future business operations. By integrating green accounting with Corporate Social Responsibility (CSR) initiatives aligned with ISO 26000 standards, PT. Coca-Cola demonstrates its commitment to environmental stewardship and social responsibility. This approach creates a win-win situation, leading to a sustainable future for the company and its surrounding community. This revised text condenses the original information while maintaining the key points about green accounting at PT. Coca-Cola, emphasizing its positive impact on environmental sustainability and business performance.